The Effects of Systematic Instruction in Teaching Multistep Social-Communication Skills to Children with Autism Spectrum Disorder Using an iPad. (18th August 2019) - Alzrayer, Nouf M.; Banda, Devender R.; Koul, Rajinder K.
ABSTRACT: Objective: Tablets have successfully been used with individuals with autism spectrum disorder (ASD) and other developmental disabilities to request preferred items, label objects, share information, and engage in social interactions. However, there are limited data on the efficacy of utilizing such devices to teach multistep social-communication skills. Method: We used nonconcurrent multiple baseline design across behaviors to examine the effectiveness of systematic instruction on teaching multistep social-communication skills using an iPad ® loaded with Proloquo2Go™. Three children between the ages of 7 and 10 years diagnosed with ASD and other developmental disabilities participated in the study. Results: To varying degrees, the participants were successful in using the iPad ® to perform a multistep sequence in requesting, saying "thank you, " and answering personal questions. Procedural modifications were made during the intervention phase for two participants so that they were able to acquire social-communication skills using AAC. Conclusions: The findings indicate that systematic instruction is effective in developing advanced social-communication skills.